Examining the mediating effect of job satisfaction on the relationship between budgetary participation and organizational citizenship behavior in Indonesian higher education institutions - Kurniawan Ali Fachrudin; Mahfud Sholihin (Cogent Business & Management, 2021)
This study aims to investigate the relationship between budgetary participation, job satisfaction, and organizational citizenship behavior. This study particularly examines if job satisfaction mediates the relationship between budgetary participation and organizational citizenship behavior of faculty members of Indonesian higher education institutions using self-determination theory. Further, this study examines whether such relationship is stable for both public and private higher education institutions. Using a positivistic-quantitative approach with survey method, we have responses from 350 faculty members, 149 are from public institutions and 201 are from private institutions. We analyzed the data using causal mediation analysis procedure and find that job satisfaction does not mediate the relationship between budgetary participation and organizational citizenship behavior. Instead, job satisfaction and budgetary are independent variables of organizational citizenship behavior. Further analysis, however, reveals that in public institutions, job satisfaction mediates the relationship between budgetary participation and organizational citizenship behavior.
Keywords: 650; Budgetary participation; Higher education; Indonesia; Job satisfaction; Organizational citizenship behavior